Employee Performance is Assessed from Placement, Career Development, Performance Assessment and Job Description - Bonaventura Setiaji; Istiatin Istiatin; Sudarwati Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine and analyze employee performance in terms of placement, career development, performance appraisal, and job description at the Sukoharjo Pratama Tax Office. The population in this study were 105 civil servants at the Sukoharjo Pratama Tax Office. The sampling technique used was a saturated sampling technique. Data were collected by questionnaire. Data analysis techniques used descriptive analysis, hypothesis testing, multiple linear regression, t-test, F-test, and R2 test with the help of SPSS for Windows Release 23. The results of this study can be concluded that placement does not affect the performance of employees at the Sukoharjo Pratama Tax Office. Career development has a significant effect on employee performance at the Sukoharjo Pratama Tax Office. Performance appraisal has a significant effect on employee performance at the Sukoharjo Pratama Tax Office. Job descriptions do not affect employee performance at the Sukoharjo Pratama Tax Office. The results of the study indicate that 56.5% of employee performance at the Sukoharjo Pratama Tax Office can be explained by the variables of placement, career development, performance appraisal, and job description, the remaining 43.5% is explained by other variables.